2016
DOI: 10.1002/hep.28352
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective β‐blockers do not affect mortality in cirrhosis patients with ascites: Post Hoc analysis of three randomized controlled trials with 1198 patients

Abstract: The safety of nonselective b-blockers (NSBBs) in advanced cirrhosis has been questioned. We used data from three satavaptan trials to examine whether NSBBs increase mortality in cirrhosis patients with ascites. The trials were conducted in 2006-2008 and included 1198 cirrhosis patients with ascites followed for 1 year. We used Cox regression to compare allcause mortality and cirrhosis-related mortality between patients who did and those who did not use NSBBs at randomization, controlling for age, gender, Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 34 publications
2
110
0
Order By: Relevance
“…In the first of these studies, a propensity score-matched study in a cohort of patients with cirrhosis on the transplant wait list showed a survival advantage of patients with refractory ascites on NSBB compared to those not on NSBB and, interestingly, showed that the use of carvedilol (a NSBB with vasodilatory properties that has been shown to lead to a larger decrease in blood pressure compared to propranolol [16] ) had an intermediate survival between patients with propranolol (lowest mortality) and those not on NSBB (highest mortality) [17] . The second study, a post-hoc analysis of data from 3 RCTs about V 2 receptor antagonists in the treatment of ascites, showed no differences in mortality between those on and off NSBB, even when adjusted by MELD, mean arterial pressure, dose of beta-blockers or study group (satavaptan vs. placebo) [18] .…”
Section: Ascitesmentioning
confidence: 99%
“…In the first of these studies, a propensity score-matched study in a cohort of patients with cirrhosis on the transplant wait list showed a survival advantage of patients with refractory ascites on NSBB compared to those not on NSBB and, interestingly, showed that the use of carvedilol (a NSBB with vasodilatory properties that has been shown to lead to a larger decrease in blood pressure compared to propranolol [16] ) had an intermediate survival between patients with propranolol (lowest mortality) and those not on NSBB (highest mortality) [17] . The second study, a post-hoc analysis of data from 3 RCTs about V 2 receptor antagonists in the treatment of ascites, showed no differences in mortality between those on and off NSBB, even when adjusted by MELD, mean arterial pressure, dose of beta-blockers or study group (satavaptan vs. placebo) [18] .…”
Section: Ascitesmentioning
confidence: 99%
“…Other retrospective studies and meta analyses could not confirm this [24][25][26], but it is nevertheless possible that in a subset of patients with refractory ascites in whom the cardiac response to hypotension may be inadequate, NSBB may lead to a disturbance in the circulatory status, and therefore the Baveno consensus meeting recommended that for the given time, NSBB should be used cautiously in case of a systolic blood pressure <90 mm Hg, serum sodium <130 mEq/L or acute kidney injury [5] . In this regard, a recent study demonstrated that there was no clinical or hemodynamic rebound after abrupt interruption of NSBB in patients with cirrhosis [27] .…”
Section: Old Strategies With New Insightsmentioning
confidence: 78%
“…According to the size, presence of red signs on varices and Child-Pugh score either traditional NSBB or EVL According to the size, presence of red signs on varices and Child-Pugh score, either traditional NSBB, EVL or carvedilol can be used (27,31) Avoidance of carvedilol in decompensated cirrhosis and caution with the use of NSBB in refractory ascites (3,6,11,15,19,20,25,26) Statins are promising (1) Hepatic vein pressure gradient-guided therapy useful but not widely available to assess response to NSBB (11,15) Carvedilol promotes greater reduction of portal hypertension when compared to propranolol, and is as efficacious or better than EVL and can be used in patients unresponsive to traditional NSBB (22,27,31) Simvastatin can lower portal hypertension …”
Section: Current Rationalementioning
confidence: 99%